A Review on Buying Behavior of Urban Consumer - Tripathi, Prashant (Innovative Research Thoughts, 2018)
Urban marketing is an indispensable element within the strategies for economic development of the cities, contributing to the overall vision of the strategy. This helps cities to accomplish many objectives (attracting new national or international companies, consolidate industrial infrastructure, developing tourism, diversifying and improving transport and health services), while they have to maintain a certain level or to cut off public expenses, and to face the harsh competition to attract new investors. The biggest challenges for urban marketing are changes occurred in market structure and dynamics, which exceed the response capacity of the cities. Taking into consideration each factor, product category has an insignificant role in influencing impulsive buying behavior. Similarly, respondents who have financial independence also have an insignificant role in influencing impulsive buying behavior. Among the factors that are significant for triggering impulsive buying behavior is availability of cash, mood of consumer, POS terminal/ATM facility, price, store layout, availability of time, product promotion, store environment and reference group. Comparative study of urban as well as rural marketing is also performed in the present study.